Development of Assessment Instruments Based on Higher order Thinking Skill (HOTS) to Measure Critical Thinking Students of Class XI IPS Private Senior High School of Sultan Iskandar Muda Medan TP 2020/2021 - Simanihuruk, Darto Paulus; Maipita, Indra; Ruslan, Dede (Budapest International Research and Critics University, 2021)
The development of a HOTS-based assessment instrument in the form of a test is prepared based on an analysis of the needs of students and teachers in economics subjects for the 2020/2021 academic year in the 2013 curriculum student critical. This research is a development research (R and D) with a Borg and Gall development model that has been adapted to research needs Based on the results of the study, it shows that the results of the evaluation expert validation for multiple choice questions of 88% are in the very good category, for essay questions 87% are in the very good category, the results of material expert validation are 84% in the very good category, the results of response validation the teacher is 88% very good and the student response validation is 91% in the very good category. For the results of the analysis of the validity of multiple-choice questions and descriptions, they are in the valid and reliable category, have a level of difficulty in the medium category and have different power of questions, namely 8 questions in the very good category, 8 questions in the good category and 9 questions in the sufficient category. The results of the analysis of students' HOTS questions have an average of 66% in the sufficient category, and the results of the students' critical thinking questionnaire have an average of 68.8% are in the critical enough category. This shows that the HOTS-based assessment instrument is effective in measuring students' critical thinking skills seen from the results of the HOTS-based assessment instrument analysis which is directly proportional to the results of students' critical thinking questionnaires.